2005
DOI: 10.1080/02699200400027189
|View full text |Cite
|
Sign up to set email alerts
|

Topic repetitiveness after traumatic brain injury: An emergent, jointly managed behaviour

Abstract: Topic repetitiveness is a common component of pragmatic impairment and a powerful contributor to social exclusion. Despite this, description, characterization and intervention remain underdeveloped. This article explores the nature of repetitiveness in traumatic brain injury (TBI). A case study of one individual after TBI provides the basis for a conceptualization of topic repetitiveness in terms of two major strands of thinking in pragmatics. Firstly, it is viewed as an emergent response to underlying deficit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Like Coelho et al (2002), Bond and Godfrey (1997) reported that the acquired brain injury (ABI) group's turns included fewer prompts (utterances meant to elicit verbal information from the listener) and more responses, and conversation partners of participants with TBI prompted more and took shorter turns. Body and Parker (2005) conducted a case study in which they also noted that the male participant with TBI took long turns on a repetitive topic.…”
Section: Turn-taking In Adults With Tbimentioning
confidence: 98%
“…Like Coelho et al (2002), Bond and Godfrey (1997) reported that the acquired brain injury (ABI) group's turns included fewer prompts (utterances meant to elicit verbal information from the listener) and more responses, and conversation partners of participants with TBI prompted more and took shorter turns. Body and Parker (2005) conducted a case study in which they also noted that the male participant with TBI took long turns on a repetitive topic.…”
Section: Turn-taking In Adults With Tbimentioning
confidence: 98%
“…It has been observed in patients with traumatic brain injury (see Body and Parker, 2005) and Fragile X without autism (Hagerman, Amiri, and Cronister, 1991;Abbeduto and Hagerman, 1997;Belser and Sudhalter, 2001;Murphy and Abbeduto, 2007). Its association with autism emerged in early practitioners' accounts which contained descriptions of children who typically spoke in monologues, displayed very asymmetrical participation in topics or obsessive preoccupation with unusual themes (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…In the case of TBI, CA research has focused on patterns in touching, silences, topic repetitiveness, and task-based talk (Barnes, 2012;Body & Parker, 2005;Bond & Godfrey, 1997;Denman & Wilkinson, 2011;Friedland & Miller, 1998). Collectively, these studies demonstrate that CA is useful for providing detailed analysis of specific communicative patterns in interaction between individuals with TBI and their familiar communication partner(s).…”
Section: Ca and Acquired Communication Disordersmentioning
confidence: 96%